EDUKASI MANFAAT AROMATERAPI LEMON DAN LAVENDER TERHADAP PENURUNAN NYERI DISMENORE PRIMER PADA REMAJA PUTRI - Nasution, Naimah; Natalia, Kristin; Krisna, Putri; Sihaloho, Wilfa Muslimah (INSTITUT KESEHATAN DELI HUSADA, 2025)
Adolescence is the transition period from childhood to adulthood, is a crucial developmental period due to rapid physical, psychological, emotional and social changes, typically occurring between the ages of 10 and 19. This period begins with puberty, one of the symptoms of which is menstruation in adolescent girls. Menstruation is the release of blood from the uterus through the vagina, which can lead to dysmenorrhea. Dysmenorrhea is menstrual pain characterized by cramps in the lower abdomen that typically occur before menstruation. This menstrual pain can range from mild to severe. This education on the benefits of lemon and lavender aromatherapy was conducted on evidence based from previous research. It was stated that lemon and lavender aromatherapy had an effect on reducing primary dysmenorrhea pain in adolescents. Therefore, this outreach was conducted with adolescents in Sidodadi Village, Deli Serdang Regency. Community service plays a crucial role in improving the quality of adolescent health. Through this activity, adolescent learned that lemon and lavender aromatherapy can reduce primary dysmenorrhea